1983
DOI: 10.1128/jb.153.2.581-587.1983
|View full text |Cite
|
Sign up to set email alerts
|

Apparent bacteriophage-binding region of an Escherichia coli K-12 outer membrane protein

Abstract: The 325-residue OmpA protein is one of the major outer membrane proteins of Escherichia coli. It serves as the receptor for several T-even-like phages and is required for the action of certain colicins and for the stabilization of mating aggregates in conjugation. We have isolated two mutant alleles of the cloned ompA gene which produce a protein that no longer functions as a phage receptor. Bacteria possessing the mutant proteins were unable to bind the phages, either reversibly or irreversibly. However, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 38 publications
(50 reference statements)
1
16
0
Order By: Relevance
“…The phage-resistant ompA mutants analyzed possess alterations at three areas of the OmpA protein: regions 70, 110, and 154. Most of the mutational alterations we found were located at region 70 (13 of 16, including the two mutants analyzed previously [13]). For this region, direct evidence that it is exposed at the cell surface has been obtained (13).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The phage-resistant ompA mutants analyzed possess alterations at three areas of the OmpA protein: regions 70, 110, and 154. Most of the mutational alterations we found were located at region 70 (13 of 16, including the two mutants analyzed previously [13]). For this region, direct evidence that it is exposed at the cell surface has been obtained (13).…”
Section: Discussionmentioning
confidence: 69%
“…The plasmids PTU105 and pTU115 have been described before (13). pTU202 and PTU203 were obtained by hydroxylamine mutagenesis (35) of pTU201, which contains the complete ompA gene cloned into pBR325 (8), followed by transformation into strain UH201.3 and selection for resistance to phage Ox2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reversible adsorption was tested by incubating a mixture of such cells consisting of a threefold excess of mutant over wild-type cells with phage. The phage neutralization rate was compared with that determined for wild-type cells alone (12,20). Strain RMT182, lacking detectable amounts of OmpA protein, was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…The results suggested that the protein is exposed at the surface of the cell at least around residues 25, 70, and 110 (numbers according to the E. coli sequence). In another, we have analyzed phage-resistant ompA mutants which produce an altered protein (12,20). The mutant proteins had alterations affecting three regions of the polypeptide, located around amino acid residues 70, 110, and 154.…”
mentioning
confidence: 99%